(untitled) (International Journal of Engineering and Computer Science, 2021)
Optical Burst Switching (OBS) is a promising paradigm for high speed transmission of data. In OBS, a key problem is to schedule bursts with minimum loss. Single method is not sufficient to improve performance. So, our performance model includes some feasible methods to improve OBS performance without significantly increasing the implementation complexity. The methods are addition of simple fiber delay lines (FDLs), increasing random extra offset time, window based channel scheduling (WBS) and Burst Delay Feedback scheduling (BDFS). Additional FDLs can only eliminate the negative impact caused by the variation of the offset time between control packets and data bursts. The random extra offset time approach does not require any additional hardware in the nodes. WBS provides better throughput improvement when FDLs are used in the nodes to compensate the processing time. Finally Burst Delay Feedback Scheduling in addition with these methods can significantly improve OBS throughput and reduce transmission delay.